2016
DOI: 10.1007/s10704-016-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical hardening rate model for predicting path-dependent ductile fracture

Abstract: A new phenomenological framework for predicting ductile fracture after non-proportional loading paths is proposed, implemented into FE software and validated experimentally for a limited set of monotonic and reverse loading conditions. Assuming that ductile fracture initiation is imminent with the formation of a shear band, a shear localization criterion in terms of the elastoplastic tangent matrix is sufficient from a theoretical point of view to predict ductile fracture after proportional and non-proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Linear damage in Eq. ( 16) was first utilized by Johnson and Cook (1985) and is also identical to definition of the so-called "damage indicator" utilized in Marcadet and Mohr (2016). Eqs.…”
Section: Damage Accumulationmentioning
confidence: 99%
“…Linear damage in Eq. ( 16) was first utilized by Johnson and Cook (1985) and is also identical to definition of the so-called "damage indicator" utilized in Marcadet and Mohr (2016). Eqs.…”
Section: Damage Accumulationmentioning
confidence: 99%
“…The evolution of isotropic hardening dr( p) is determined by the Voce isotropic law defined as (Eq. (9)) [45]:…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…Berto et al 26 applied an energy-based approach to simulate the damage behaviour of a notched specimen under torsion loading. Recent studies [27][28][29] have suggested that not only the damage evolution law but also an accurate plasticity description is important for modelling damage behaviour in complex loadings. Depending on the application, the advanced plasticity model may have to consider the stress state, anisotropy, and kinematic hardening to accurately describe the stress-strain behaviour of material under complex loading conditions.…”
Section: Introductionmentioning
confidence: 99%